Coexistence of Aortic Pseudocoarctation and Mitral Valve Perforation in a Patient With Takayasu’s Arteritis: Coincidence or Association? - Hülya PEYNİRCİ CERŞİT and Sinan CERŞİT (Archives of Rheumatology, 2019)
Takayasu’s arteritis (TA) is a rare idiopathic inflammatory condition that predominantly involves the aorta and its branches causing narrowing and aneurysms in vessels. In this case report, we present TA with a rare coexistence of aortic pseudocoarctation and anterior mitral leaflet perforation with moderate regurgitation.